Candidemia among Hospitalized Pediatric Patients Caused by Several Clonal Lineages of Candida parapsilosis - Rasmus Krøger Hare; Amir Arastehfar; Søren Rosendahl; Arezoo Charsizadeh; Farnaz Daneshnia; Hamid Eshaghi; Hossein Mirhendi; Teun Boekhout; Ferry Hagen; Maiken Cavling Arendrup (Journal of Fungi, 2022)
Candida parapsilosis is the second most common cause of candidemia in some geographical areas and in children in particular. Yet, the proportion among children varies, for example, from 10.4% in Denmark to 24.7% in Tehran, Iran. As this species is also known to cause hospital outbreaks, we explored if the relatively high number of C. parapsilosis pediatric cases in Tehran could in part be explained by undiscovered clonal outbreaks. Among 56 C. parapsilosis complex isolates, 50 C. parapsilosis were genotyped by Amplified Fragment Length Polymorphism (AFLP) fingerprinting and microsatellite typing and analyzed for nucleotide polymorphisms by FKS1 and ERG11 sequencing. AFLP fingerprinting grouped Iranian isolates in two main clusters. Microsatellite typing separated the isolates into five clonal lineages, of which four were shared with Danish isolates, and with no correlation to the AFLP patterns. ERG11 and FKS1 sequencing revealed few polymorphisms in ERG11 leading to amino-acid substitutions (D133Y, Q250K, I302T, and R398I), with no influence on azole-susceptibilities. Collectively, this study demonstrated that there were no clonal outbreaks at the Iranian pediatric ward. Although possible transmission of a diverse C. parapsilosis community within the hospital cannot be ruled out, the study also emphasizes the necessity of applying appropriately discriminatory methods for outbreak investigation.